ALK7 protects against pathological cardiac hypertrophy in mice. (6th August 2015) - Huang, He; Tang, Yanhong; Wu, Gang; Mei, Yang; Liu, Wanli; Liu, Xiaoxiong; Wan, Nian; Liu, Yu; Huang, Congxin
Abstract: Aims: Activin receptor-like kinase 7 (ALK7), one of the type I transforming growth factor-β receptors, is expressed in various tissues, including the heart. However, the participation of ALK7 in the regulation of cardiac hypertrophy has not yet been studied. Here, we sought to determine the regulatory role and underlying mechanisms of ALK7 in cardiac hypertrophy. Methods and results: We performed aortic banding (AB) in ALK7-knockout mice, cardiac-specific ALK7-transgenic mice, and the wild-type littermates of these mice. Cardiac hypertrophy was evaluated using pathological analysis, echocardiographic measurement, haemodynamic measurement, and molecular analysis. Our results revealed that ALK7 disruption led to an aggravated cardiac hypertrophic response that was accompanied by increased cardiac fibrosis and reduced contractile function, whereas cardiac-specific ALK7 overexpression exhibited the opposite phenotype in response to pressure overload. Similarly, ALK7 protected against angiotensin II-induced cardiomyocyte hypertrophy in vitro . Mechanistically, we demonstrated that ALK7-dependent cardioprotection was mediated largely through inhibition of the MEK–ERK1/2 signalling pathway. Conclusion: Our data suggest that ALK7 acts as a novel regulator of pathological cardiac hypertrophy via the negative regulation of MEK–ERK1/2 signalling and may serve as a potential therapeutic target for pathological cardiac hypertrophy.